Natural and Combination Fish Aggregating Devices (FADS) as Tools for Fish Aggregation in Lake Kenyir, Trengganu, Malaysia - Sakri Ibrahim; Julaihi Matusin; Sukree Hajisamae (ASEAN Journal on Science and Technology for Development, 2000)
Natural and Combination Fish Aggregating Devices (FADS) as Tools for Fish Aggregation in Lake Kenyir, Trengganu, Malaysia